Hermeneutika Hukum Islam Abû Ishâq Al-Syâthibî - Kurdi Fadal (Al-Ulum, 2010)
This paper traces al-Syatibi’s thought about how he formulated the ijtihad of hermeneutics that aims to make Islamic law could really be applied by every Muslim. Sharia is set to benefit for both in this life and hereafter. Therefore, every legal system is aimed to organize all aspects of human life must be able to give benefit to them. Therefore, methodological steps must be taken every jurist, mujtahid or legal reviewers when they are about to set the law. The first step profoundly understands the texts of the Koran and Hadiths; knows the context of the emergence of these texts, as well as understands the context of a community, e.g. legal subjects, so, the legal can be applied and beneficial.